The relationship between remnant cholesterol and young-onset myocardial infarction in patients with type 2 diabetes: a retrospective study - Gao, Yajie; Lei, Tianjiao; Dang, Peizhu; Li, Yongxin (Frontiers in Pharmacology, 2025)
BackgroundRemnant cholesterol (RC) has emerged as a novel therapeutic target beyond low-destiny-lipoproteins cholesterol (LDL-c). While elevated RC levels are strongly associated with cardiovascular disease risk in the general population, their specific role in young-onset acute myocardial infarction (AMI) among patients with type 2 diabetes mellitus (T2DM) remains insufficiently explored and warrants further investigation.MethodsThis retrospective study included AMI patients with T2DM admitted to the First Affiliated Hospital of Xi’an Jiaotong University from 2018 to 2022. Patients were stratified into tertiles according to RC levels and compared using thresholds derived the commanded values from the PREDIMED cohort study. The primary outcome was young-onset AMI. Group differences were analyzed using the chi-square test and the Kruskal–Wallis H test, while Spearman correlation analyses assessed relationships between variables. Univariate and multivariate logistic regression analyses were employed to evaluate the association between RC and young-onset AMI.ResultsAmong the 2,514 participants (mean age 61.58 ± 11.15 years), 802 (31.9%) had young-onset AMI. The increase of young-onset AMI increased significantly with rising RC levels (27.0% vs 29.7% vs 39.1%, P < 0.001). RC showed significant positive correlation with total cholesterol (TC, r = 0.497, P < 0.001), triglycerides (TG, r = 0.411, P < 0.001), and LDL-c (r = 0.166, P < 0.001). RC was independently associated with a higher risk of young-onset AMI (OR: 1.579; 95% CI: 1.354–1.842; P < 0.001), even after adjusting for other traditional risk factors of cardiovascular disease (OR: 1.415; 95% CI 1.189–1.684; P < 0.001). Notably, RC levels remained strongly linked to young-onset AMI regardless of whether LDL-c levels were within the desired range.ConclusionRC is a significant and independent risk factor for young-onset AMI in T2DM patients, irrespective of LDL-c level. These findings underscore the importance of monitoring and managing RC levels in clinical practice to mitigate cardiovascular risk in this population.